Prior Appendectomy and the Onset and Course of Crohn’s Disease in Chinese Patients - Dafan Chen; Jing Ma; Qiwen Ben; Lungen Lu; Xinjian Wan (Gastroenterology Research and Practice)
Background and Aim. The relationship between prior appendectomy and Crohn’s disease (CD) has previously revealed conflicting findings. The present study investigates the relationship between prior appendectomy and CD development in Chinese patients. Methods. A retrospective case-control study was performed to compare prior appendectomy rate between CD patients and age- and gender-matched controls at two Chinese hospitals. The clinical course of CD was determined in patients who underwent and did not undergo appendectomies before CD diagnosis. Results. A total of 617 CD patients and 617 controls were included. The appendectomy rate before CD diagnosis in patients was higher, when compared to controls (6.65% versus 3.73%, P=0.033). Appendectomy was a risk factor for the onset of CD independent of smoking in the multivariate analysis (OR: 1.878; 95% CI: 1.111–3.174; P=0.019). Appendectomies were performed closer to the date of CD diagnosis in the trend test (P=0.039). The rate of appendectomy within one year or 1-5 years before CD diagnosis was higher in patients when compared to that in controls (0.97% versus 0%, P=0.031; 1.13% versus 0.32%, P=0.180). However, the rate of appendectomy over five years before CD diagnosis was close to controls (4.54% versus 3.40%, P=0.392). No significant differences in disease location, behavior, medication, and intestinal resection between appendectomy and nonappendectomy CD patients were found, even in the subgroup analysis by age of appendectomy. Conclusion. Prior appendectomy is a risk factor for the onset of CD. However, the appendectomy rate only increased for a short duration before CD diagnosis, likely reflecting a diagnostic bias. Prior appendectomy did not influence the features or course of CD.